A narrative review of new research progress regarding the use of airway stents in benign airway stenosis. Issue 6 (3rd June 2022) - Zou, Hai; Zhang, Jun; Zhan, Kan; Mou, Xiao-Zhou; Zhu, Biao
ABSTRACT: Introduction: Benign airway stenosis is a severe disease that can result in death with improper treatment. Clinicians must know about airway stents to choose the best one in their daily practice. Areas covered: PubMed, Embase, and other electronic databases and websites were searched to identify relevant randomized controlled trials and meta-analyses. This review summarizes different types of airway stents and analyzes their advantages and disadvantages. Expert opinion: Increasing attention has been given to the indications and prognosis of benign airway stenosis treated with different airway stents. With more investigations and data, better alternatives to silicone stents could be developed in the future.